The Influence of the “Hayah Karima” Initiative on the Standard of Living of Egyptian Citizens: Evidence from the Menofia Governorate - sharara, merihan (AUC Knowledge Fountain, 2023)
Social protection programs have been used in several developing countries in order to aid in their development efforts. In Egypt, “Hayah Karima”, an initiative which represents a developmental initiative endorsed by Egypt’s President Al-Sisi, aims to minimize the developmental gaps among citizens in terms of standards of living. “Hayah Karima” is based on governmental finance in partnership with the private sector. This paper covers this initiative and its different aspects as well as their possible impact on the standards of living for citizens in El- Menofia Governorate. The paper also includes 71 surveys conducted with different partners and beneficiaries of the initiative. The conducted interviews with the selected sample took place through different mediums such as face-to-face interviews, phone calls, emails, and via mail. The sample consists of citizens, non- governmental organizations, private sector and governmental bodies within sectors such as healthcare, education, civil services, and infrastructure. The results show that villages, Ashmoun and El-Shohada, in El-Menofia governorate were among those that benefited the most from “Hayah Karima” initiative in all its aspects of service, especially in education as well as the decentralization of access to civil services (issuing birth certificates...etc.). However, delays in the implementation of some of the planned interventions were reported. ‘Hayah Karima’ initiative is relatively not studied intensively in development research, hence more focus towards it is recommended for future research in the field of social protection in Egypt.